Sexual Orientation Disparities in Pregnancy and Infant Outcomes - Everett, Bethany G. (Matern Child Health J, 2019)
OBJECTIVES: Little is known about maternal and infant health among sexual minority women (SMW), despite the large body of research documenting their multiple preconception risk factors. This study used data from the 2006-2015 National Survey of Family Growth (NSFG) to investigate sexual orientation inequities in pregnancy and birth outcomes, including miscarriage, stillbirth, preterm birth, and birth weight. METHODS: Women reported 19,955 study eligible pregnancies and 15,996 singleton live births. Sexual orientation was measured using self-reported identity and histories of same-sex sexual experiences (heterosexual-WSM [women who only report sex with men]; heterosexual-WSW [women who report sex with women]; bisexual, and lesbian). Logistic regression models were used that adjusted for several maternal characteristics. RESULTS: Compared to heterosexual-WSM, heterosexual-WSW (OR=1.25, 95% CI =1.00, 1.58) and bisexual and lesbian women (OR=1.77, 95% CI=1.34, 2.35) were more likely to report miscarriage, and bisexual and lesbian women were more likely to report a pregnancy ending in stillbirth (OR=2.85, 95% CI=1.40, 5.83). Lesbian women were more likely to report low birth weight infants (OR=2.64, 95% CI=1.38, 5.07) and bisexual and lesbian women were more likely to report very preterm births (OR=1.84, 95% CI= 1.11, 3.04) compared to heterosexual-WSM. CONCLUSIONS: This study documents significant sexual orientation inequities in pregnancy and birth outcomes. More research is needed to understand the mechanisms that underlie disparate outcomes and to develop interventions to improve sexual minority women’s maternal and infant health.